(NfOMA gORDEEW(B: [(NpOWESTX(B] /s - (NgORXKIJ(B, (NmAKSIMs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1980)
(Nw KNIGU a(B. (Nm(B. (NgORXKOGO (B(1868-1936) (NWHODQT POWESTX (B"(NfOMA gORDEEW(B" (1899) (NI RASSKAZY (B1892-1897 (NGODOW(B.s
(NrASSKAZY (B1892-1897 (NGODOW(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs